Pengaruh Konflik di Laut China Selatan terhadap Keamanan Maritim Indonesia - Muhammad Haikal Rama Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
The South China Sea (SCS) conflict is one of the most complex geopolitical disputes in the Southeast Asian region, involving not only claimant countries such as China, the Philippines, and Vietnam, but also impacting non-claimant countries such as Indonesia. Although Indonesia is not officially involved in the territorial claim dispute in the SCS, its geographical position close to the disputed area, especially around the Natuna Islands, places Indonesia in a strategic and vulnerable position. This journal discusses in depth Indonesia's position in the SCS conflict, highlighting how Indonesia maintains its territorial sovereignty without being directly involved in the conflict. In addition, the direct impact of the conflict on Indonesia's maritime security is also discussed, including increasing territorial violations, threats to local fishermen, and challenges in monitoring territorial waters. The conflict in the SCS also has an impact on regional stability and Indonesia's maritime economy, especially in the context of ASEAN cooperation and the world's maritime axis policy. Finally, this journal reviews various efforts made by Indonesia in maintaining its maritime security, such as strengthening diplomacy, modernizing defense equipment, and developing an integrated maritime policy. Through a qualitative approach and descriptive analysis, this journal aims to provide a comprehensive understanding of the dynamics of the SCS conflict and its implications for Indonesia's maritime security.